Different responses to environmental factors in terpene composition of Pinus heldreichii and P. peuce: ecological and chemotaxonomic considerations - Rajčević, Nemanja; Nikolić, Biljana; Marin, Petar D. (Archives of Biological Sciences, 2019)
Paper description: There are no studies on the influence of environmental factors and their correlation with pine oleoresin composition from the leaves of several Balkan pines. Oleoresins were isolated from Bosnian and Macedonian pine collected from nine localities, including two sympatric. The obtained composition was analyzed statistically to assess the correlation with bioclimatic, geological and geographical parameters. Three chemotypes were present in Bosnian pine leaf oleoresins, while only one was found in Macedonian pine. While the oleoresin profiles showed strong species-dependent composition and variability, environmental factors, including geological substrate type and exposition must also be taken into account. Abstract: Many studies show the influence of the environment on terpene composition, but not many of them deal with the terpene composition variability in correlation with environmental factors in Pinus. We chose two endemic species – P. heldreichii Christ. (Bosnian pine) and P. peuce Griseb. (Macedonian pine) – two relict and (sub)endemic species of the Balkan peninsula. They mainly form pure stands but can appear in mixed populations, most commonly with each other. These species belong to different subgenera and thus differ greatly, especially in needle anatomy. α-pinene, limonene and germacrene D predominated in Bosnian pine leaf oleoresins, while Macedonian pine oleoresin contained high amounts of α-pinene. Furthermore, there were three chemotypes present in Bosnian, and only one in Macedonian pine. Oleoresins of Bosnian pine did not show correlation with climate, however, its composition changed in response to geological substrate type. Macedonian pine oleoresin showed a high correlation with the climate but changed only a little in response to geological substrate type. The oleoresin profiles showed strong species-dependent composition and variability. However, since each species expressed different responses to tested environmental conditions, it is important to take into consideration these variables when analyzing natural populations of the species. https://doi.org/10.2298/ABS190705045R Received: July 5, 2019; Revised: July 18, 2019; Accepted: July 24, 2019; Published online: August 1, 2019 How to cite this article: Rajčević N, Nikolić B, Marin PD. Different responses to environmental factors in terpene composition of Pinus heldreichii and P. peuce: Ecological and chemotaxonomic considerations. Arch Biol Sci. 2019;71(4):629-37.